Water and Wastewater Services in the Danube Region : FYR Macedonia Country Note - World Bank (Washington, DC, 2015)
To evaluate the sustainability of services in the region, an overall sector sustainability assessment was done taking into account four main dimensions: access to services, quality of services, efficiency of services, and financing of services. Each of these dimensions is measured through three simple and objective indicators. For each indicator, best practice values are established by looking at the best performers in the region, and countries closest to those best performers are deemed to have a more mature sector. A more complete description of the methodology to assess sector sustainability is included in the annex of the state of the sector regional report from the Danube Water Program. The outcomes of this assessment for the FYR Macedonia water sector are presented in Figure 9, which also shows average and best practices in the Danube region. The Macedonian sector sustainability score is 61, which is below the Danube average of 64. The assessment shows that, on average, the country performs well in terms of access to piped water and flush toilets, continuity of service, staffing level, and affordability. The main deficiencies of the FYR Macedonia water sector identified through the sector sustainability assessment are investment level, operating cost ratio, wastewater treatment coverage, and the nonrevenue water level. The main sector challenges are: securing a multiyear investment budget; improving the efficiency of service providers; and implementing fully the existing water laws.